Mortality after emergency abdominal surgery in a non‐metropolitan Australian centre. (25th November 2018) - Tocaciu, Shreya; Thiagarajan, Jayaraman; Maddern, Guy J.; Wichmann, Matthias W.
Abstract: Objective: Emergency abdominal surgery has poorer outcomes and higher mortality rates, compared with elective surgery. Serious morbidity or mortality occurs in up to 40% of patients. No information is available with regard to the outcome of patients undergoing emergency abdominal surgery in rural Australia. Methods: Patients undergoing emergency abdominal surgery in a 110‐bed rural surgical centre in South Australia over a 5 year period (January 2010–December 2014) were included in the study. Patient data were retrieved using the hospital database and review of patient records. Results: A total of 4396 general surgical emergency admissions was recorded. Emergency admissions without intervention, endoscopic intervention only, appendectomy, cholecystectomy or urological or gynaecological diagnoses were excluded from mortality analysis. The remaining 237 patients underwent major abdominal emergency surgery for bowel obstruction (benign and malignant: n  = 143, 60%), injury/inflammation/perforation/peritonitis ( n  = 85, 36%) or haemorrhage/ischaemia ( n  = 9, 3.8%). Thirty‐ ( n  = 9) and 90‐ ( n  = 12) day mortality rates were 3.8% and 5.1%, respectively. Conclusion: Emergency abdominal surgery can be safely provided in non‐metropolitan Australian centres, with a low 30‐day mortality rate of 3.8% and a 90‐day mortality rate of 5.1%. This compares well with results published by other national and international investigators.